2023
DOI: 10.1186/s12967-023-04231-2
|View full text |Cite
|
Sign up to set email alerts
|

Atrial epicardial adipose tissue abundantly secretes myeloperoxidase and activates atrial fibroblasts in patients with atrial fibrillation

Abstract: Background Epicardial adipose tissue (EAT) secretome induces fibrosis. Fibrosis, primarily extracellular matrix (ECM) produced by fibroblasts, creates a substrate for atrial fibrillation (AF). Whether the EAT secretome from patients with AF activates human atrial fibroblasts and through which components, remains unexplored. Research aims (a) To investigate if the EAT secretome from patients with versus without AF increases ECM production in atrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…3 I). We further identified genes associated with fibrosis, including FN1 (encoding fibronectin), GAS6 (encoding growth arrest-specific 6), COL1A2 (encoding collagen, type I, alpha 2), ACTA2 (encoding actin alpha 2), and POSTN (encoding periostin) [ [30] , [31] , [32] , [33] ], which were significantly increased in the OCTN2-deficient group ( Fig. 3 J).…”
Section: Resultsmentioning
confidence: 99%
“…3 I). We further identified genes associated with fibrosis, including FN1 (encoding fibronectin), GAS6 (encoding growth arrest-specific 6), COL1A2 (encoding collagen, type I, alpha 2), ACTA2 (encoding actin alpha 2), and POSTN (encoding periostin) [ [30] , [31] , [32] , [33] ], which were significantly increased in the OCTN2-deficient group ( Fig. 3 J).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, inflammatory processes in EAT have been recently associated with AF onset [77][78][79][80]. EAT adiponectin signaling [81] and EAT-driven endothelial dysfunction [82] can influence AF vulnerability.…”
Section: The Role Of the Embryonic Epicardium In Adult Electrophysiol...mentioning
confidence: 99%
“…In addition to their interaction with endothelial cells, neutrophils can also interact with cardiomyocytes, promoting apoptosis and activating atrial fibroblasts, which results in increased fibrous tissue [95,96]. Recent studies utilizing single-cell transcriptomics have identified different subpopulations of neutrophils at various stages of healing after myocardial infarction, all of which share a unique sialic acid binding Ig-like lectin F (SiglecFhi) signature [97].…”
Section: Neutrophilsmentioning
confidence: 99%